A gate of night - Forrest, Bella (Forrest, Bella. Shade of vampire, 2014)
Welcome back to The Shade ... Derek and Sofia are finally enjoying a well-deserved break. Staying at a resort with good food, sun and sea, Sofia is thrilled to witness Derek's re-introduction to the human world. They would almost be mistaken for a normal young couple, if it were not for the red-eyed monster lurking in the shadows and watching their every move, waiting for his signal to pounce.